The Inducible Accumulation of Cell Wall-Bound p-Hydroxybenzoates Is Involved in the Regulation of Gravitropic Response of Poplar - Zhao, Yunjun; Yu, Xiao-Hong; Liu, Chang-Jun (Frontiers in Plant Science, 2021)
Lignin in Populus species is acylated with p-hydroxybenzoates. Monolignol p-hydroxybenzoyltransferase 1 (PHBMT1) mediates p-hydroxybenzoylation of syringly alcohol, eventually leading to the modification of syringyl lignin subunits. Angiosperm trees upon gravistimulation respond with the re-orientation of their growth along with production of specialized secondary xylem, i.e., tension wood, that. generates tensile force to pull the inclined stem or leaning branch upward. Sporadic evidence suggests that angiosperm tension wood contains relatively a high percentage of syringyl lignin and lignin-bound p-hydroxybenzoates. However, whether such lignin modification plays a role in gravitropic response remains unclear. By imposing mechanical bending and/or gravitropic stimuli to the hybrid aspens in the wild type, lignin p-hydroxybenzoate deficient, and p-hydroxybenzoate overproduction plants, we examined the responses of plants to gravitropic/mechanical stress and their cell wall composition changes. We revealed that mechanical bending or gravitropic stimulation not only induced the overproduction of crystalline cellulose fibers and elevated the relative abundance of syringyl lignin, but also significantly induced the expression of PHBMT1 and the increased accumulation of p-hydroxybenzoates in tension wood. Furthermore, we found that although disturbing lignin-bound p-hydroxybenzoate accumulation in the PHBMT1 knockout and overexpression poplars did not alter the major cell wall chemical composition shifts in their tension wood as occurred in the wild type plants, depletion of p-hydroxybenzoates intensified the gravitropic curving of the plantlets in response to gravistimulation, evident with the enhanced stem secant bending angle; in contrast, over-accumulation of p-hydroxybenzoates mitigated gravitropic response. These data suggest that PHBMT1-mediated lignin modification is involved in the regulation of poplar gravitropic response and, likely by compromising gravitropism or enhancing autotropism, negatively coordinates the action of tension wood cellulose fibers to control poplar wood deformation and plant growth.